Social Media and the Mediatization of Politics in Poland: Changing Communication Strategies of Politicians in The Digital Age - Aleksandra MŁOCZKOWSKA (Communications of International Proceedings, 2025)
The article addresses the topic of the mediatization of politics in Poland and the growing role of social media in politicians' communication strategies. This study focuses on the analysis of the role of mediatization in Polish political life, with particular emphasis on the importance of social media in shaping the image of politicians and in the conduct of election campaigns. The paper presents the results of a survey of two Lodz parliamentarians - a member of the Polish Parliament and a senator - conducted by means of content analysis, casual interviews and participant observation. In addition, data on the activity of Polish political parties and politicians on platforms such as Facebook, X and TikTok were reviewed. The results indicate a clear tendency to intensify political activities in the digital space, which is reflected in the adaptation of communication strategies to the requirements of modern media.
Keywords: mediatization of politics; social media; election campaign; political communication; parliamentarians; politician image